Gas-gap heat switches with negative room temperature conductor separation and their application to ultra-low temperature platforms. (March 2023) - Poole, T.; Foster, T.; Matthews, A.J.
Abstract: Controlling the thermal conductance between different temperature stages in a cryogenic system is a common problem. Often the desire is to achieve a high conductance during a pre-cooling phase, and a low conductance during a running phase. Here, we describe a novel method for constructing gas-gap heat switches: the design exploits the difference in thermal contraction of two materials to obtain a narrow (μm scale), tuneable, gas-gap at low temperature. We find that the measured temperature-dependent thermal conductance is in reasonable agreement with a simple thermal model and the switches have a sufficiently low 'off' conductance to be compatible with dilution refrigerator systems operating below 5 mK. A 'remote' sorption pump also allows the system to operate at elevated temperatures >30 K. We demonstrate the application of these switches for rapid sample exchange on cryogen-free dilution refrigerator systems, where a sample loaded from room temperature can be cooled to below 20 mK in under 3.5 hours. Highlights: Construction of thermal contraction gas-gap heat switches with negative room temperature conductor separation. Efficient cool down of cryogen-free systems from high temperature. Retaining the ability to control these systems over wide temperature ranges.